Thermal analysis of nanofluid flow within porous enclosure with curved hot wall utilizing numerical approach. (May 2023) - Tan, Xinhua; Altoum, Sami H.; Othman, Hakeem A.; Syam, Muhammed I.; Salman, M.A.; Musa, Awad
Abstract: To evaluate the efficiency of a system involving wavy shapes of wall, numerical technique has been utilized in this article. The region between two wavy complex surfaces was fabricated from porous material and the working fluid is nanofluid (mixture of water with various shapes of alumina nanoparticles). The new terms related to porous media have been added according to Darcy law. The pressure terms were removed with defining stream function. The last form of equations contains two variables (θ and Ψ) which were solved via CVFEM. The results from the present code have been compared with previous article and good agreement was reported. With augmenting Ha, the speed of nanofluid decreases and Nu drops about 50.48% when Ra = 700. Considering greater buoyancy force makes Nu to increase about 61.36% when Ha = 0. The shape factor has a direct relation with the amount of conductivity, thus, Nu enhances about 11.97% with an increase of this factor when Ha = 15, Ra = 150.